Gender-specific interactions of MTHFR C677T and MTRR A66G polymorphisms with overweight/obesity on serum lipid levels in a Chinese Han population. Issue 1 (December 2016) - Zhi, Xueyuan; Yang, Boyi; Fan, Shujun; Wang, Yanxun; Wei, Jian; Zheng, Quanmei; Sun, Guifan
Abstract Background Little is known regarding the interactions of methylenetetrahydrofolate reductase (MTHFR ) C677T and methionine synthase reductase (MTRR ) A66G polymorphisms with overweight/obesity on serum lipid profiles. The aim of the current study was to explore interactions between the two polymorphisms and overweight/obesity on four common lipid levels in a Chinese Han population and further to evaluate whether these interactions exhibit gender-specificity. Methods A total of 2239 participants (750 females and 1489 males) were enrolled into this study. The genotypes of theMTHFR C677T andMTRR A66G were determined by a TaqMan assay. Overweight and obesity were defined as a body mass index between 24 and 27.99 and ≥ 28 kg/m2, respectively. The interactions were examined by factorial design covariance analysis, and further multiple comparisons were conducted by Bonferroni correction. Results There was no significant difference in the genotypic and allelic frequencies between females and males (MTHFR 677 T allele: 54.47 % for females and 54.40 % for males;MTRR 66G allele: 24.73 % for females and 24.71 % for males). Interaction between theMTHFR C677T polymorphism and overweight/obesity on serum triglyceride levels, and interaction between theMTRR A66G polymorphism and overweight/obesity on serum high-density lipoprotein cholesterol levels were detected in women (P = 0.015 andP = 0.056, respectively). For female subjects with overweight/obesity, the serum triglyceride levels inMTHFR 677TT genotype [1.09 (0.78–1.50) mmol/L] were significantly higher as compared withMTHFR 677CC genotype [0.90 (0.60–1.15) mmol/L, P = 0.007], and theMTRR 66GG genotype carriers had higher serum high-density lipoprotein cholesterol levels than those withMTRR 66AG genotype (1.46 ± 0.50 vs. 1.19 ± 0.31 mmol/L, P = 0.058). Furthermore, in male subjects with overweight/obesity, theMTHFR 677CT genotype carriers had higher low-density lipoprotein cholesterol levels than those withMTHFR 677TT genotype (2.96 ± 1.07 vs. 2.74 ± 0.88 mmol/L, P = 0.015). Conclusions Our results indicate that there exist interactive effects of theMTHFR C677T andMTRR A66G polymorphisms with overweight/obesity on some lipid traits in Chinese Han population, and the effects were gender-specific.